Entoloma tianmushanense sp. nov. (Entolomataceae) from Mount Tianmu (Zhejiang, Eastern China) - Shen, Yuyu; Li, Wen-Qian; Pang, Chun-Mei; Dai, Wen-Hong; Song, Yao-Bin; Dong, Ming (Phytotaxa, 2024)
Entoloma tianmushanense, a new species belonging to Entolomataceae, is described from Zhejiang Province, China. The phylogenetic tree based on ITS and LSU sequences indicated that Entoloma tianmushanense forms clusters within Rhodopolia clade in the subgenus Entoloma. Morphologically this new species is mainly characterized by it is medium-size, mustard brown, or nougat with darker center, sticky when moist in pileus, spores with 5(–6) pronounced angles and elongated apiculus, with clamp connections and slightly pale brown pigment occasionally in pileipellis. The new species is described and illustrated, as well as compared to other congeneric species.